2014
DOI: 10.4000/rei.5812
|View full text |Cite
|
Sign up to set email alerts
|

Innovation ouverte et évolution des business models dans les pôles de compétitivité : le rôle des intermédiaires dans la création variétale végétale

Abstract: Référence électronique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 61 publications
0
6
0
4
Order By: Relevance
“…However, 13 papers dive deeper into a discussion of regional characteristics. We have been able to identify two regional factors which may play a role in cluster innovativeness: the preexisting relations between cluster actors (Sellitto and Burgess 2005;Viljamaa 2007;Parto 2008;Eklinder-Frick et al 2012Gretzinger and Royer 2014;Leroux et al 2014) and the resource endowment defining the historical evolution and orientation of the regional economy (Sellitto and Burgess 2005;Callagher 2012;Calzonetti et al 2012;Zettinig and Vincze 2012;Basco and Calabrò 2016;Kim and Shim 2018). These papers have shown the importance of a deep understanding of the regional context and demonstrated that there can be no common recipe for success as the pre-existing conditions in each location are unique.…”
Section: 11mentioning
confidence: 97%
See 1 more Smart Citation
“…However, 13 papers dive deeper into a discussion of regional characteristics. We have been able to identify two regional factors which may play a role in cluster innovativeness: the preexisting relations between cluster actors (Sellitto and Burgess 2005;Viljamaa 2007;Parto 2008;Eklinder-Frick et al 2012Gretzinger and Royer 2014;Leroux et al 2014) and the resource endowment defining the historical evolution and orientation of the regional economy (Sellitto and Burgess 2005;Callagher 2012;Calzonetti et al 2012;Zettinig and Vincze 2012;Basco and Calabrò 2016;Kim and Shim 2018). These papers have shown the importance of a deep understanding of the regional context and demonstrated that there can be no common recipe for success as the pre-existing conditions in each location are unique.…”
Section: 11mentioning
confidence: 97%
“…This brings us to the second important dimension of the reviewed articles. Thus, our analysis allowed to identify three key roles which different actors may assume in the cluster: facilitators (Eklinder-Frick et al 2012, Connell et al 2014, Leroux et al 2014, Burger et al 2015, Castro 2015, Giest 2015, Aslesen and Pettersen 2017, sponsors and/or stakeholders (Arthurs et al 2009, Giest 2015, Berkowitz 2018, Zhong and Tang 2018 as well as visionaries or champions (Klofsten et al 2015, Wei et al 2016, Yström and Aspenberg 2017. The facilitation role can include a broad range of activities such as the creation of conditions conducive to knowledge sharing, collective learning, trustand capability-building (e.g.…”
Section: 21mentioning
confidence: 99%
“…Leurs modalités d'intermédiation consistent notamment à renseigner les organisations sur d'éventuels nouveaux partenaires, à organiser des transactions entre deux parties ou plus, à agir comme un médiateur entre les partenaires lorsque la collaboration est déjà amorcée, à trouver des conseils et des financements pour les offres innovantes résultant de ces collaborations (Howells, 2006) 3 . Les intermédiaires d'innovation contribuent également à favoriser des pratiques d'innovation ouverte en instaurant des relations de confiance entre les acteurs, en facilitant la circulation des ressources et des connaissances à l'intérieur et à l'extérieur du groupe de partenaires, et en animant ce groupe (Leroux et al, 2014). Ils sont alors qualifiés d'intermédiaires d'innovation ouverte.…”
Section: -Revue De Littératureunclassified
“…De nouvelles pratiques se développent alors. L'Open Innovation est tout spécialement une illustration d'un mouvement de reconfiguration de l'organisation de la recherche de la part des entreprises (Chesbrough, 2006 ;Leroux et al, 2014).…”
Section: Renouveau Des Concours : Un Premier éClairageunclassified